Non-Litigation Dispute Resolution Based on Labor Law in Indonesia - Hanifah, Ida (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
Law Number 2 of 2004 concerning the resolution of Industrial Relations issues, among other things, determines the resolution of industrial relations disputes, through litigation and non-litigation channels, which regulates the mechanism for resolving disputes through litigation, which consists of procedures for lawsuits in the Industrial Relations Court at the Court. State and appeal to the Supreme Court of the Republic of Indonesia. The procedure used to collect data in this research is documentation, namely the guidelines used in the form of notes or quotations, searches for legal literature, books and other things related to the identification of problems in this research both offline and online. Analysis of legal materials is carried out using a content analysis method (centent analysis method) which is carried out by explaining the material on legal events or legal products in detail to facilitate interpretation in the discussion. Law Number 13 of 2003 concerning Employment and Law Number 2 of 2004 concerning solving Industrial Relations problems are the basis for resolving disputes between workers and employers. The collective agreement must be registered by the parties making the agreement in the Industrial Relations court at the District Court in the area where the parties entered into the collective agreement. If within 30 working days one of the parties refuses to negotiate or negotiations have been carried out but no agreement has been reached, bipartite negotiations deemed to have failed. If bipartite negotiation efforts fail, one or both parties will register their dispute with the agency responsible for the local employment sector by attaching evidence that bipartite efforts have been made. If such evidence is not attached, the agency responsible for the field of local labor force must return the files to be completed no later than within (seven) working days from the date of return of the files and every bipartite negotiation must be made into minutes signed by the parties